PENGUKURAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN (STUDI PADA RUMAH MAKAN CEPAT SAJI OLIVE FRIED CHICKEN DI JALAN GLAGAHSARI YOGYAKARTA) - Deviona, Amadea; Adhilla, Fitroh (Jurnal Fokus Manajemen Bisnis, 2015)
This study aims to find out how the influence of quality service to customer satisfaction Olive fried chicken at Glagahsari Yogyakarta. And to find out what variables are influentialsignificant to customer satisfaction both partially and simultaneously. Primary data obtained from the results of the distribution of questionnaires to consumers who consume at Olive fried chicken at Glagahsari Yogyakarta, sample and sampling techniques using the side accidental method and purposive sampling. And selected consumers aged over 17 years. Processing the data of this research is using multivariate statistical methods. with technique multiple linear regression analysis, partial test (t test), and simultaneous test (F test). Partial Test Results (t test) variables of food quality (X2), communication (X4), and benefit relationship (X5) does not affect customer satisfaction (Y). While for physical environment variables (X1), customer orientation (X3), and price (X6) it was concluded that the partial test (t test) had an effect on satisfaction customer (Y) in consuming Olive freid chicken at Glagahsari Yogyakarta. From the calculation results of the simultaneous test (F test), obtained Sig <Î± = 5% or 0,000 <5%, because Sig <Î± = 5%. Then it can be concluded that the variable physical environment (X1), food quality (X2), customer orientation (X3), communication (X4), the benefits of the relationship (X5), and price (X6) that simultaneously test (F test) effect on customer satisfaction (Y) Olive fried fast food restaurant chicken at Glagahsari Yogyakarta.